Study on Permeability of Soil-Rock Mixture in Water-Blocking Layer of Open-Pit Coal Mine Dump Site - Boyu Luan; Wei Zhou; Xin Meng; Xiang Lu; Zhichao Liu (Advances in Civil Engineering)
Constructing a water-blocking layer in the dump sites of an open-pit coal mine is of great significance to improve the water retention capacity of the reclamation area. The permeability law of the water-blocking layer is costly to be analyzed and researched by means of field tests. In this study, the soil-rock mixture samples similar to the water-blocking layer were prepared, and the rock block proportion (RBP) and hydraulic pressure were adopted as test variables to conduct a permeability test, which provided theoretical support for on-site construction. The results show that when the hydraulic pressure is less than the confining pressure, the permeability increases at a steady rate as the rock block proportion increases. When the hydraulic pressure is close to or equal to the confining pressure, penetrating cracks are easily formed between the soil-rock interfaces of the sample with a higher rock block proportion, resulting in a rapid increase in permeability. With the increase of hydraulic pressure, the migration of the internal fine particles in the sample with a rock block proportion of 40% or less leads to the partial cracks closure, which gradually reduces the permeability. The internal structure of the sample with a rock block proportion more than 40% experiences a process in which the permeability decreases with the crack closure to a significant increase due to the penetrating crack formation. In summary, the soil-rock mixture with about 30% rock block proportion is characterized by suitable permeability and stability, which guarantees the construction cost on-site at the same time. In addition, increasing the rolling times of the truck can increase the compaction of the water-blocking layer and reduce the permeability. The roughness and gradation of the rock blocks can improve the permeability and stability of the water-blocking layer.